Mediating Role of Customer Satisfaction between Service Quality and Customer Loyalty with Non-Interest Bank in Nigeria - Sulaiman, Sagir Muhammad; Muhammad, Muhammad Abdulaziz; Muhammad, Aliyu Dahiru; Sabiu, Tasiu Tijjani (Universitas Muhammadiyah Yogyakarta, 2021)
The world has become a global village as competition among banks is now intense. Globalization is fuelling increased competition in Nigerian banking industry and as a result, banks are challenged to adopt customer centred strategies that would enable them to gain customer loyalty, maximize profitability and survive the competition. There is no business that survives without customers’ patronage and Islamic banks are not an exception. Customers are key stakeholders to the survival of any business, thus, satisfying the customer through providing high quality services is core to Islamic banking business. The aim of the study is to examine the mediating role of customer satisfaction in investigating the relationship between service quality and customer loyalty in non-interest bank i.e. Jaiz Bank of Kano state metropolis, Nigeria. The variance based (SEM) technique is employed in analyzing the hypothesized model of the study. Service quality positively and significantly influences customer satisfaction and customer loyalty, whereas, customer satisfaction does not significantly mediate the relationship between service quality and customer loyalty among customers of Jaiz bank in Kano state metropolis, Nigeria. The study recommends for providing high quality service in order to achieved maximum loyalty from the customers. It was further recommended on the need for reviving of the existing regulatory bodies or institutions that will ensure proper implementation of good service quality delivery among non-interest banks in Nigeria.